Reallocation the role of budget institutions. (OECD, 2005)
In recent years, reallocation has become increasingly important as a means to finance new needs in the spheres of internal and external security, integration of immigrants, education, health and pensions, especially in countries where economic growth has been weak. At a time when public expenditure is undergoing change to accommodate new needs, this report studies the impact of four institutions of the budget process upon reallocation: medium-term expenditure frameworks, rules of budgetary discipline, the role of the minister of finance, and program review. It develops a micro-economic classification of public expenditures and gives insight into the shifting pattern of central government expenditure in the last 20 years in 12 selected OECD countries (Canada, Czech Republic, France, Germany, Italy, Mexico, Netherlands, New Zealand, Spain, Sweden, United Kingdom, United States) on the basis of that classification.--Publisher's description.